Future health - Kostenius, Catrine (Luleå tekniska universitet, Hälsa och rehabilitering, 2018)
Good health has always been crucial to people’s life situation.Throughout the history of health care, cures for diseaseshave been discovered, and great strides have been made toallow humans to live longer and healthier lives. However, newchallenges arise, for example, mental ill-health in childrenand young adults, coping with an older population, and servicingsparsely populated areas, such as the Arctic regions.Moreover, increased migration brings unique challenges andliving in a digital world increase health risks. However, inevery challenge, there is an opportunity. At LTU, health is aprioritized area, with a focus on innovative interdisciplinaryresearch, for example, including the perspective of health inArctic living, widening educational research to include healthpromotion, and exploring technology within the e-health field.One possible approach is to support people to increase controlover and improve their health at individual and organizationallevels, as well as using social innovations to promotehealth with a “cool” northern perspective.